2014
DOI: 10.1007/s00438-014-0815-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of alternative splicing, alternative polyadenylation and the expression of the two KIN genes from cytoplasmic male sterility cabbage (Brassica oleracea L. var. capitata L.)

Abstract: The KIN genes are crucial members of the cold-regulated gene family. They play exclusive roles during the developmental processes of many organs and respond to various abiotic stresses in plants. However, little is known about the regulation of KIN gene expression in cytoplasmic male sterility (CMS) cabbages (Brassica oleracea L. var. capitata L.). We carried out a genome-wide analysis to identify the KIN genes in the CMS cabbage. Two non-redundant KIN genes, named BoKIN1 (Bol021262) and BoKIN2 (Bol030498), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…2 a). This is consistent with what has been observed for other Kin family members such as BN28 of Brassica napus 32 and BoKIN1 of B. oleracea 33 and is also consistent with its proposed role in the process of cold acclimation, wherein the leaf seems to bear the major brunt of cold stress compared to root and stem. These results are therefore suggestive that BoCRP1 have role in imparting cold tolerance that was further validated through its functional characterization in cold susceptible tomato.…”
Section: Discussionsupporting
confidence: 91%
“…2 a). This is consistent with what has been observed for other Kin family members such as BN28 of Brassica napus 32 and BoKIN1 of B. oleracea 33 and is also consistent with its proposed role in the process of cold acclimation, wherein the leaf seems to bear the major brunt of cold stress compared to root and stem. These results are therefore suggestive that BoCRP1 have role in imparting cold tolerance that was further validated through its functional characterization in cold susceptible tomato.…”
Section: Discussionsupporting
confidence: 91%
“…2a). This is consistent with what has been observed for other Kin family members such as BN28 of Brassica napus 31 and BoKIN1 of B. oleracea 32 and is also consistent with its proposed role in the process of cold acclimation, wherein the leaf seems to bear the major brunt of cold stress compared to root and stem. These results are therefore suggestive of BoCRP1 role in imparting cold tolerance that was further validated through its functional characterization in cold susceptible tomato.…”
Section: Discussionsupporting
confidence: 91%
“…Paralogs are genes in the same genome created by gene duplication events that may have different functions (Thornton and DeSalle 2000). Tao et al (2014) observed that two paralogous genes from B. oleracea L. var. capitata L. (BoKIN1 and BoKIN2) showed discrepancies not only in their expression patterns and transcript levels, but also in premRNA processing.…”
Section: Discussionmentioning
confidence: 99%